Low-temperature combustion and autoignition - Pilling, M. J. (Comprehensive chemical kinetics, 1997)
Combustion has played a central role in the development of our civilization which it maintains today as its predominant source of energy. The aim of this book is to provide an understanding of both fundamental and applied aspects of low-temperature combustion chemistry and autoignition. The topic is rooted in classical observational science and has grown, through an increasing understanding of the linkage of the phenomenology to coupled chemical reactions, to quite profound advances in the chemical kinetics of both complex and elementary reactions. The driving force has been both the intrinsic interest of an old and intriguing phenomenon and the centrality of its applications to our economic prosperity. The volume provides a coherent view of the subject while, at the same time, each chapter is self-contained.